12‐3: Investigation of Fingerprint on Display Technology for FLI Display. Issue 1 (28th June 2022) - Xu, Chuan X.; Yao, Qi; Tian, Wen H.; He, Wei; Li, Xiang; Yang, Ming; Li, Bing Y.; Lin, Zheng R.; Shu, Shi; Yuan, Guang C.
Abstract : We developed pinhole matrix optical solution of fingerprint on display technology for FLI OLED to avoid its low module transmittance. We investigated the influence of pinhole size and touch metal lines on the fingerprint on FLI technology in both regid and foldable display based on a 6.2inch QHD resolution OLED panel.